Effect Of Combination Decafeinated Green Tea and Green Coffee In Reducing Cholesterol Levels In Patients With Metabolic Syndrome - Alfata, Fandy Hazzy; Rohman, Mohammad Saifur; Astiawati, Tri; Tjahjono, Cholid Tri; Martini, Heny (Universitas Brawijaya, 2023)
Background: Green tea and green coffee are natural ingredients that improve cholesterol levels. Combining the two in experimental animal studies provides more significant benefits when compared to single administration in reducing cholesterol levels.Objective: This study aimed to determine the effect of decaffeinated green tea and green coffee as adjuvant treatments in reducing blood cholesterol levels.Methods: This randomized controlled trial included 90 metabolic syndrome patients determined according to the IDF criteria for Asian people aged 50–70. All subjects received atorvastatin 20 mg and were divided into three groups. Participants in Group 1 received decaffeinated green tea and green coffee 2.5 grams twice daily, Group 2 received 5 grams daily, and Group 3 received a placebo. The total cholesterol, low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL), and triglyceride levels were measured at the beginning and the end of the study.Results: At 90 days, after administration of the extract of decaffeinated green tea and green coffee, we found that the concentration of total cholesterol in Group 1 and Group 2 was significantly reduced compared to the placebo (-50 ± 6.1 vs. -62.8 ± 5.9 vs. -22.5 ± 5.8 mg/dL; p= <0.05). But there was no significant difference in reduction of total cholesterol levels between the first and second groups. The other parameters also decreased, but not significantly compared to the placebo group.Conclusion: Administration of a combination of decaffeinated green tea extract and green coffee as an adjunctive therapy can reduce the average total cholesterol, LDL, HDL, and triglyceride levels more than placebo, but only total cholesterol has a significant difference compared to other cholesterol components.